2017
DOI: 10.1002/adfm.201704476
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Transited Lysozyme as a Universal Route to Bioactive Hydroxyapatite Crystalline Film

Abstract: A key factor for successful design of bioactive complex, organic-inorganic hybrid biomaterials is the facilitation and control of adhesion at interfaces, as many current synthetic biomaterials are inert, lacking interfacial bio activity. In this regard, the development of a simple, unified way to bio functionalize diverse organic and inorganic materials toward biomineralization remains a critical challenge. In this report, a universal biomimetic mineralization route that can be applied to virtually any type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
112
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 67 publications
3
112
0
Order By: Relevance
“…2019, 31,1903973 www.advmat.de www.advancedsciencenews.com that the PTL nanofilm had excellent interfacial bioactivity to induce in situ interfacial biomineralization of HAp in simulated body fluid, [34] the remineralization inside the lyso-PEG nanofilm-coated DTs could be rationally expected (Figure 5a). Due to the small size of lyso-PEG oligomers (around 30 nm), oligomers could easily access into the deep regions of DTs and the lyso-PEG coating formed in minutes, offering a sample and effective route to build active layer inside DTs.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 92%
See 4 more Smart Citations
“…2019, 31,1903973 www.advmat.de www.advancedsciencenews.com that the PTL nanofilm had excellent interfacial bioactivity to induce in situ interfacial biomineralization of HAp in simulated body fluid, [34] the remineralization inside the lyso-PEG nanofilm-coated DTs could be rationally expected (Figure 5a). Due to the small size of lyso-PEG oligomers (around 30 nm), oligomers could easily access into the deep regions of DTs and the lyso-PEG coating formed in minutes, offering a sample and effective route to build active layer inside DTs.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 92%
“…[35] Consistently, Raman analysis of the modified surface of the DTs also indicated that the regenerated mineral was HAp rather than other calcium phosphate ( Figure S21, Supporting Information), showing typical HAp peaks of OPO vibration at 586 cm −1 and PO stretching vibration at 960 cm −1 , being consistent with dentin. [40] However, in contrast to conventional HAp growth on a surface, the remineralization on the lyso-PEG coating did not weaken the stability of mineral layers, because the lyso-PEG coating provided a robust interface between HAp crystals and underlying substrate due to the robust amyloid-mediated interfacial adhesion, in which the cumulative weight loss and the wear rate of the HAp on the amyloid-like lysozyme nanofilm-coated Ti were ten times smaller than those on the sample of HAp growth on blank Ti; [34] moreover, the HAp on the amyloid-like lysozyme nanofilm-coated Ti remained stable after strong ultrasonication (50 kHz, 200 W) for 1 h or the peeling utilizing a commercial 3 m Scotch adhesive tape to have an adhesive strength higher than 1.23 N cm −1 . Notably, the minerals precipitating within the tubules were located more than 60 ± 5 µm beneath the surface, which was at least six times deeper than that in previous reports.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
See 3 more Smart Citations